Understanding university students’ perceptions of the group work-based activity to enhance collaborative problem-solving skills and its impact on academic writing performance - Siti Anisah; Nunung Suryati (Universitas Islam Negeri Palangka Raya, Indonesia, 2025)
Group work-based activity is commonly used by teachers, primarily to improve students' learning achievement. Despite its strengths in enhancing students' abilities during language learning, yet, limited literature explores how this activity can develop students' soft skills, particularly in higher education. This study aims to explore students' perceptions of group work-based activity to enhance collaborative problem-solving skills and how group work-based activity affects their academic writing performance. Thirty-two master's students from one of the universities in Malang, Indonesia, who have been enrolled in the Writing for Publication course, are involved in this mixed-method study. The quantitative data were collected through a questionnaire and analyzed using descriptive statistics, while the results from an open-ended interview were analyzed thematically. The findings indicated that students perceive group work differently. Even though some of them stated that it was less effective, most of them agreed that this activity helped them to improve their collaborative problem-solving skills, guiding them to compose a good-quality research article. Furthermore, these findings provide new insights for teachers into how group work as a learning method can be better applied in EFL classroom practices to support 21st-century learning.